CRITICAL THINKING DISPOSITIONS - Torebek А.B.,; Tashkenbay G.T., (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Critical thinking today is not just an individual typological characteristic of a person, but a criterion according to which the heads of prestigious firms select employees. The importance of this ability is written on the Internet, in periodicals, and in the media. Teaching critical thinking helps a person to work with a continuously growing flow of information, to distinguish truth from lies, to correctly interpret the facts presented to him and formulate conclusions.